The governance of a community garden with a food cycle in suburban Tokyo. Issue 1 (7th July 2021) - Shimpo, Naomi
Abstract: Urbanites can learn more about food cycles by growing vegetables and fruits and composting food residues within a community garden (CG). Case studies are necessary for developing theories about the sustainable governance of CGs containing food cycles. In particular, Asian cities have high potential to establish food cycles because of their mixture of urban and rural land use. This paper discusses the governance of a suburban‐Tokyo CG, where neighborhood kitchen wastes were collected and used as direct fertilizer for the soil. The quantitative and qualitative data obtained through interviews and internal material of the garden was analyzed to grasp the garden's history, stakeholders' involvement, and the relationships between gardeners and kitchen waste providers. The results showed that the founder started the garden in a bottom‐up way and overcame challenges by maintaining a strong motivation and a flexible attitude. The gardeners provided work opportunities to people with disabilities and education materials to children. These collaborations may have corroborated the necessity of the garden existence. Most of the gardeners and all the waste providers live within 2 km of the garden and the close communication between them was possible, which may have maintained the kitchen waste quality. This study demonstrates advantages and challenges in the governance of Japanese CGs; however, further case studies are necessary for improving the generalizability of this study's findings. Core Ideas: Community gardens (CGs) are a potential way to establish a food cycle. This study examined the governance of a Japanese CG that recycled kitchen wastes. The garden founder had a strong motivation and a flexible attitude. The food cycle produced activities that involved local institutions. Close communication could help maintain waste separation quality.